Exploring Local Knowledge of Climate Change: Some Reflections - Chapagain, Binod K; Subedi, Ramu; Paudel, Naya Sharma (Journal of Forest and Livelihood, 2009)
This paper brings forth people's observations, feelings and perceptions of climate change and its impact on diverse aspects of rural life. It is based on interviews with individuals and groups from different socio?ecological settings across the country. The analysis suggests that the impact of climate change is ubiquitous, ranging from change in climate variability, rainfall pattern, vegetation composition, animal breeding and farming to increased human health risks and diseases. Although local people have been observing these changes for years, they have little understanding of the anthropogenic causes of these changes. Their observations and interpretations of the situation largely corroborate the scientific studies of the issue. Given the highly complex and overarching nature of climate change impact, any climate impact studies must integrate the experiential aspects and interpretative methodologies with traditional scientific approaches. In the meantime, climate change responses need to be initiated with the local knowledge, even without waiting for scientific studies. Key words: climate change, knowledge, perception, livelihoods, forest resources Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.106-110